Temozolomide in combination with carbon ion or photon irradiation in glioblastoma multiforme cell lines: does scheduling matter? - Harrabi, Semi B.; Combs, Stephanie; Brons, Stephan; Haberer, Thomas; Debus, Jürgen; Weber, Klaus-Josef (International journal of radiation biology, 2013)
Purpose: To extend the application area of particle therapy with carbon ions the many already established treatment regimens for different tumor entities have to be taken into consideration. The present study investigates the effect of combined radiochemotherapy with temozolomide (TMZ) and high linear energy transfer (LET) irradiation with carbon ions versus photons.Materials and methods: Clonogenic survival was analyzed for human glioma cell lines with different O6-methylguanine-DNA methyltransferase (MGMT) status, LN18 (MGMT+) and LN-229 (MGMT-), after exposure to different doses of either carbon ion or photon irradiation at different time points relative to TMZ application. Cell cycle distribution was measured by flow cytometry. MGMT status of the cell lines was verified by Western blot.Results: LN-18 and LN-229 reacted in accordance to their MGMT status with different sensitivity to TMZ treatment. Combined treatment with irradiation showed additive cytotoxic effects for both cell lines with low radiation doses but no radiosensitization. With increasing photon doses the combination effect was reduced, and the efficacy of the combined treatment was not dependent on administration schedule. Carbon ion irradiation showed the well known increased relative biological efficiency (RBE), overcame the abovementioned antagonism and was also not schedule-dependent.Conclusions: The in vitro effectiveness of TMZ in combined radiochemotherapy is independent of administration time or MGMT-expression. Both cell lines are significantly more sensitive to combined treatment with carbon ion radiation than to photon radiation but do not show any super-additive effects.